PERAN PENGELOLA SEKOLAH DALAM KEPEMIMPINAN MELALUI BUDAYA DAN CITRA DI MASA PANDEMI COVID 19 - Diajeng Herika Hermanu (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2022)
The purpose of this study is to analyze the relationship between the variables of school management leadership style, school culture, and school image during the Covid 19 pandemic based on the perceptions of teachers.The research method used is the relational survey model. An online survey strategy was used in this study. In this study there are four parts of the data collection tool used, namely data in the form of personal information, leadership scale using the Multifactor Leadership Questionnaire (MLQ) scale, school culture survey scale (School Culture Survey) (SCS), and school image assessment scale (Assessment of School Image) (AoSI). The data were analyzed using the Mix Method program. Frequency and percentage scores were calculated to determine the demographic characteristics of teachers (gender, education level, seniority, and current school tenure). With these demographic characteristics, Correlation and Forecasting Method will be carried out. In data analysis, arithmetic means, standard deviation, frequency, Pearson's correlation, regression, Path analysis, and Sobel test for significance were used.The results showed that the leadership manifested by the principal who created a positive effect on organizational members and school culture also contributed positively to the organizational image of educational institutions.